DESIGN AND ANALYSIS OF PATCHOULI STEM CHOPPER MACHINE USING DOUBLE BLADE KNIFE TO IMPROVE PATCHOULI OIL PRODUCTIVITY - Sir Anderson; Syafira Salsabila; Nasirwan Nasirwan; Mulyadi Mulyadi; syukri syukri (Jurnal Ilmiah Poli Rekayasa, 2026)
The global demand for patchouli essential oil (Pogostemon cablin Benth.) continues to grow, with Indonesia supplying approximately 70% of world demand. One critical pre-distillation process that significantly affects oil yield is the size reduction of patchouli stems. Manual chopping is time-consuming and labor-intensive, leading to production inefficiencies. This study presents the design of a patchouli stem chopper machine intended to improve patchouli oil productivity. The design methodology begins with problem identification, followed by conceptual design using morphological matrix, component calculations, and 3D modelling using SolidWorks 2020. The machine is powered by a ¼ HP AC electric motor at 1400 rpm, reduced through a pulley-belt transmission system to achieve a blade rotational speed of 525 rpm. A double-blade planer knife type was selected due to its superior cutting performance compared to the circular knife type. Calculation results show that the machine achieves a theoretical capacity of 156 kg/h with a blade cutting force of 686.41 N, shaft diameter of 25 mm (minimum 20.93 mm by Rankine theory), V-belt length of 1.7 m, key dimensions of 6×5×20 mm, and a bearing nominal lifetime of 37,044,000 hours. The use of a double-blade planer configuration offers a novelty in bidirectional cutting ability, differentiating this design from previous gasoline-engine-based machines. It should be noted that the capacity of 156 kg/h is a theoretical value derived from design calculations and has not yet been validated through actual field or laboratory testing. Field validation of the prototype's actual performance remains a limitation of this study and is recommended for future work. The machine is expected to reduce labor requirements and increase patchouli oil production efficiency.